EMC for Product Designers - Williams, Tim (Newnes, 2014)
EMC for Product Designers: Meeting the European EMC Directives is a six-chapter text that considers the by-product of the co-existence of all kinds of radio services, called electromagnetic compatibility (EMC). This book discusses the solution to the damaging frequency interference of EMC and the problem of EMC to electronic equipment. The opening chapter considers the effect of adapting the EMC Directives to decrease the economic damage being caused by electromagnetic interference, as well as the analysis, definition, and compliance of EMC and EMC Directives. The next chapters deal with the measurement of EMC; RF emission testing; features of circuits, layout, and grounding; digital and analogue circuit design; and description of interfaces, filtering, and shielding. These topics are followed by discussion of the equipment for mains harmonic emission, the facilities and equipment for measuring RF susceptibility, and the transient susceptibility to ESD. The concluding chapters examine the use of performance criteria in measuring EMC. These chapters describe the features and application of the Fourier spectrum. The book can provide useful information to economists, engineers, radio technicians, students, and researchers.